Perlindungan Hukum Konsumen Dalam Kontrak Jual Beli (Studi Perbandingan Hukum Indonesia dan Thailand) - Wardiansyah, Kris; Andini, Aulia Marsya; Fardiillah, Roni (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Consumer protection within contract law is vital to modern legal systems, especially in Indonesia and Thailand, where rapid economic growth presents unique challenges. Safeguarding consumer rights in sales and purchase agreements has become increasingly significant, underscoring the necessity for a comparative analysis of the legal frameworks in both nations. Objective: This study aims to compare the systems of consumer contract protection in Indonesia and Thailand, with a particular emphasis on the legal framework, protection mechanisms, implementation, and practices in sales and purchase transactions. Method: Employing a normative juridical approach and comparative analysis, the study investigates and contrasts both countries' consumer protection legal systems to identify their similarities and differences. Results: The findings indicate that Indonesia and Thailand share fundamental consumer protection principles, but their implementation strategies differ considerably. Indonesia adopts a comprehensive approach through Law No. 8 of 1999, whereas Thailand integrates consumer protection measures across various sectoral regulations, with a strong emphasis on alternative dispute resolution. Conclusion and Recommendations: Both countries are committed to consumer protection, albeit through differing legal frameworks. Indonesia could enhance its alternative dispute resolution mechanisms, while Thailand might benefit from consolidating its sectoral regulations to achieve greater consistency in consumer protection.